Preparation and Research of Solvent-Free Epoxy Coating for Drinking Water Tank. Issue 2 (March 2020) - Cui, Cancan; Shi, Jiafeng; Kang, Shaowei; Han, Zhongzhi; Zhang, Jing; Sun, Zhaoxing; Duan, Shaoming; Liu, Benhua; Guo, Xiaojun
Abstract: By compounding E42 and E51 epoxy resin, blending modified polyamide curing agent and modified fatty amine curing agent, optimizing glycidyl ether reactive diluent system, using safe non-toxic pigment filler and grading wear resistance filling and optimization auxiliaries system, the developed coating sanitary index meets the requirements of "Sanitary Standard for Drinking Water", and the wear resistance (cs17, 1000g/1000r, mg) is 64.4mg. The coatings passed 6J impact resistance test and is resistant to bending 1.5° without cracks. The coatings also have excellent resistance to medium corrosion and salt spray.